Mathematical methods for physics and engineering - Riley, K F (Cambridge University, 2015)
The new edition of this highly acclaimed textbook contains several major additions, including more than four hundred new exercises (with hints and answers). The authors have included a preliminary chapter covering areas such as polynomial equations, trigonometric identities, and coordinate geometry, as well as two separate chapters for statistics and probability.